BUDAYA ALIH BAHASA MASYARAKAT URBAN DALAM MEMAHAMI INTERNET DENGAN METODE BORROWING - Sri Widiastutik (Journal Social and Humaniora, 2017)
Massive use of the Internet creates problems in the transfer of the language of the urban community, because it needs a method of borrowing as a way out for the enrichment of Indonesian variety by reducing the risk of negative impacts of the use of language uptake in communication in student environment STIKI Denpasar as IT-based High School. This research is conducted qualitative and quantitative approach with Linguistic study. There are also data collection techniques conducted by observation, documentation, interview and FGD. Level of accuracy of data sources based on information on: Characteristics of ICT term in conversation, Student reactions to the use of ICT terms, and the impact of ICT language transfer using Borrowing method. Implementation of Borrowing method is a smart solution to cultivate knowledge about how to use the term uptake of ICT for urban adolescents can more easily and practically apply the internet, without damaging the Indonesian order is good and right. Students are able to provide the right information to the public. Keywods: Borrowing; the term Absorption; Information & Computer Technology